Perancangan Sistem Informasi Parkir dengan WiFi Berbasis Arduino - Yulianto, Novi; Bacharuddin, Fahraini (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2016)
Now the need for access to information is very important because the information obtained can specify or provide comfort and ease in performing daily activities. One example is to use gadgets such as smartphones, notebooks, tablets and others, we can easily find out information directly without having to come to the venue. This system aims to design information systems in the parking lot. This technology can provide an idea of ??the amount of available parking spots has been filled or empty. By accessing the IP address given earlier, then we will know the availability of parking space directly. From the test results, it can be said that this system has the advantages of easy to use, the application is simple and can help improve the comfort / convenience for users of the car park. But this system also has the disadvantage of a webserver which is used has a very small memory that can not be accessed by many concurrent users in one time.
Keywords: Tempat parkir otomatis; Webserver; Microcontroller WiDo